Funciones ejecutivas en los estudiantes de la Unidad Educativa Amelia Gallegos Díaz, Riobamba - Basantes Cherrez, Gabriela Katherine (2021)
The aim of this research was to analyze the level of neuropsychological maturity of the executive functions in male and female students of Fifth Year of General Basic Education, parallels A and B, of the “Amelia Gallegos Díaz” Educational Unit. The executive functions are a set of cognitive abilities that are necessary to control and self-regulate one’s own behavior. A quantitative approach was implemented as a methodology, a non-experimental design was used, the type of research by level or scope was descriptive, for the objectives it was basic, for the place it was on field, the sample size was intentional and non-probabilistic since it was established with 60 students of the Fifth Year of General Basic Education, parallels A and B of the “Amelia Gallegos Díaz” Educational Unit. The technique and instrument for data collection was the ENFEN test, concluding that male and female students have a very low level of neuropsychological maturity, that is, they have a weakening in their executive functions, causing impulsive reactions and school failure.